An atypical manifestation of a common familiar tumour: the unforeseen occurrence of osteochondroma - Devanathan, Udayakumar; Muralidassan, Abhiraami; Kuppan, Naveenkumar; Kumarsamy, Manikandan; Nandana, Gauri (International Journal of Research in Orthopaedics, 2024)
A solitary osteochondroma in the lesser trochanter is an exceedingly rare occurrence. The nature of osteochondromas as benign osteocartilaginous tumours is typically regarded as a developmental anomaly rather than a neoplastic condition. Patients afflicted with this condition may experience a range of symptoms dependent upon the size of the tumour, with limited range of motion being a common manifestation. The present case study pertains to a distinctive instance of a benign solitary osteochondroma of the lesser trochanter, which was diagnosed and treated through an excisional biopsy using a Hardinge approach.